Distinct Spiking Patterns of Excitatory and Inhibitory Neurons and LFP Oscillations in Prefrontal Cortex During Sensory Discrimination - Tseng, Hua-an; Han, Xue (Frontiers in Physiology, 2021)
Prefrontal cortex (PFC) spike activity and local field potential (LFP) oscillation dynamics are broadly linked to various aspects of behavior. PFC neurons can encode the identity of sensory stimuli and related behavioral outcome in a range of sensory discrimination tasks. However, it remains largely unclear how different neuron subtypes and related LFP oscillation features are modulated in mice during sensory discrimination. To understand how excitatory and inhibitory neurons in PFC are selectively engaged during sensory discrimination and how they relate to LFPs oscillations, we used tetrode devices to probe well isolated individual PFC neurons, and LFP oscillations, in mice performing a three-choice auditory discrimination task. We found that a majority of the PFC neurons, 78% of a total of 711 individual neurons, exhibited sensory evoked responses that are context and task-progression dependent. Using spike waveforms, we classified these responsive neurons into excitatory and inhibitory neurons, and found that both neuron subtypes were transiently modulated, with individual neurons’ responses peaking throughout the entire task duration. While the number of responsive excitatory neurons remain largely constant throughout the task, an increasing fraction of inhibitory neurons were gradually recruited as trial progressed. Further examination of the coherences between individual neurons and LFPs revealed that inhibitory neurons in general exhibit higher spike-field coherence with LFP oscillations than excitatory neurons, first at higher gamma frequencies at the beginning of the task, and then at theta frequencies during the task, and finally across theta, beta and gamma frequencies at task completion. Together, our results demonstrate that while PFC excitatory neurons are continuously engaged during sensory discrimination, PFC inhibitory neurons are preferentially engaged as task progresses and selectively coordinated with distinct LFP oscillations. These results demonstrate increasing involvement of inhibitory neurons in shaping the overall PFC network dynamics as sensory discrimination progressed towards completion.